1983
DOI: 10.3109/00365598309182133
|View full text |Cite
|
Sign up to set email alerts
|

Serum Testosterone, LH, and FSH in Patients with Testicular Cancer Before and After Radio- and Chemotherapy

Abstract: Serum levels of testosterone, luteinizing hormone and follicle-stimulating hormone were measured in 73 patients with germ cell testicular cancer in stages I and II. Blood samples were taken after unilateral orchidectomy but immediately before irradiation and chemotherapy, and again 1 to 3 years after cessation of therapy. No difference was found between pre- and post-treatment testosterone values. Patients who received radiotherapy only, had similar pre- and post-treatment luteinizing hormone values, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…After unilateral orchidectomy, decreased testosterone levels were found in 5‐34% of patients, probably due to preexisting abnormalities in the remaining testicle 28‐31. However, normal sexual functioning is possible even with very low serum testosterone levels (6‐12 nmol/L),32, 33 and it has been shown that erection can still occur even after castration 34, 35.…”
Section: Treatment‐related Biologic‐organic Influences On Sexual Funcmentioning
confidence: 99%
“…After unilateral orchidectomy, decreased testosterone levels were found in 5‐34% of patients, probably due to preexisting abnormalities in the remaining testicle 28‐31. However, normal sexual functioning is possible even with very low serum testosterone levels (6‐12 nmol/L),32, 33 and it has been shown that erection can still occur even after castration 34, 35.…”
Section: Treatment‐related Biologic‐organic Influences On Sexual Funcmentioning
confidence: 99%
“…Particularly, pregnant ewes with twins or multiple fetuses always encounter undernutrition during late gestation, since feed intake dramatically declines due to the increased volume of uterus and extruded abdomen while the nutrition requirement significantly elevates because of fetal growth and development. Previous studies revealed that undernutrition disrupted metabolic homeostasis and induced serious lipid metabolism disorders in maternal and fetal livers [ 2 4 ], which may induce maternal diseases and fetal growth retardation and maldevelopment [ 5 7 ]. However, little information is known about the effect of undernutrition on ruminal homeostasis in spite of the fact that ruminal homeostasis is the basis for the metabolism, development, and health of ruminants [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them originated from the treatment of leukaemic infiltrates in the testes of pre-pubertal boys, indicating that a dose of 24 Gy given to this age group may cause irreversible damage to the endocrine function of the testis [24]. In addition, previous data have indicated that not only the spermatogenesis but also the activity of Leydig cells in the contralateral gonad may be impaired [3], making them even more sensitive to harmful effects. After the first patients with CIS had been irradiated, a group from Manchester [43] published their data on irradiation of the contralateral testis of 49 seminoma patients.…”
Section: Radiation Dosementioning
confidence: 99%